Magnetic damping constant in Co-based full heusler alloy epitaxial films. (8th April 2015) - Oogane, M; Kubota, T; Naganuma, H; Ando, Y
Abstract: Co-based full-Heusler alloys, such as Co2 MnSi and Co2 MnGe, are expected to be used as half-metallic ferromagnetic material, which has complete spin polarization. They are the most promising materials for realizing half-metallicity at room temperature due to their high Curie temperature. The optimization of the magnetic damping constant of ferromagnetic materials is extremely important for achieving high-speed magnetization switching and reducing critical current density for spin torque transfer switching. We have systematically investigated the magnetic damping constant in Co-based full Heusler alloy epitaxial films. We found that the Gilbert damping constant seems to be roughly proportional to the total density of states at the Fermi level ( E F ) by first principle calculation. A very small magnetic damping constant of 0.003 in the Co2 Fe0.4 Mn0.6 Si epitaxial film was demonstrated. The small magnetic damping constant in Co2 Fe x Mn1− x Si films with x < 0.6 can be attributed to the half-metallicity of Heusler alloys. Co-based full Heusler alloys with both half-metallicity and small magnetic damping will be very useful for future applications based on spintronic devices.